Insight into the Copper-Catalyzed Borylation of Strained Alkenes - Parra, Alejandro; López, Aurora; Díaz-Tendero, Sergio; Amenós, Laura; Ruano, José Luis García; Tortosa, Mariola (Synlett, 2015)
The copper-catalyzed hydro- and carboboration of strained alkenes is presented. The reaction is highly diastereoselective and affords boronic ester derivatives many of which are difficult to synthesize by known methods. Competition experiments with different alkenes show that high levels of chemoselectivity can be achieved. Density functional theory calculations are in agreement with the observed chemoselectivity.
Keywords: bicyclic compounds; boron; catalysis; chemoselectivity; copper